Book review of: Kaminer, Tahl; Ma, Leonard; Runting, Helen (Hrsg.) (2023): Urbanizing Suburbia. Hyper-Gentrification, the Financialization of Housing and the Remaking of the Outer European City - Diller, Christian (Raumforschung und Raumordnung | Spatial Research and Planning, 2023)
Book review.